Synchrotron emission from nanowire array targets irradiated by ultraintense laser pulses. (5th June 2018) - Martinez, B; d'Humières, E; Gremillet, L
Abstract: We present a numerical study, based on two-dimensional particle-in-cell simulations, of the synchrotron emission induced during the interaction of femtosecond laser pulses of intensities I  = 10 21 –10 23 W cm −2 with nanowire arrays. Through an extensive parametric scan on the target parameters, we identify and characterize several dominant radiation mechanisms, mainly depending on the transparency or opacity of the plasma produced by the wire expansion. At I  = 10 22 W m −2, the emission of high-energy (>10 keV) photons attains a maximum conversion efficiency of ∼10% for 36–50 nm wire widths and 1 μ m interspacing. This maximum radiation yield is found to be similar to that achieved in a uniform plasma of same average (sub-solid) density, but nanowire arrays provide efficient radiation sources over a broader parameter range. Moreover, we examine the variations of the photon spectra with the laser intensity and the wire material, and we demonstrate that the radiation efficiency can be further enhanced by adding a plasma mirror at the backside of the nanowire array. Finally, we briefly consider the influence of a finite laser focal spot and oblique incidence angle.